Caracterizacion de sitios degradados y adaptabilidad de especies forestales en el ambito de Pucallpa, Ucayali - Soudre, M.; Ricse, A.; Sabogal, C.; Kobayashi, S.; Guariguata, Manuel R.; Alegre, J. (2002)
This article is a result of a research project to characterize degrated sites in Pucallpa, Peru and determine the adaptability of six native tree species in areas abandoned after agricultural use. Nine farmers were selected for setting-up experimental plots on abandoned land characterized by Ultisols on flat terrain with low biomass (4-8 t/ha) and dominated by invading weed species: Imperata brasiliensis (cashupsha), Rottboellia conchinchinensis (arrocillo) and Baccharis floribunda (sachahuaca). Six tree species (treatment) were randomly planted in the plots following a statistical design with repetitions by strata (dominant weed species). A control plot of young secondary growth was included. The tree species used are Amburana cearensis (ishpingo), calycophyllum spruceanum (capurena negra), Cedrelinga catenaeformis (tornillo), Schizolobium amazonicum (pashaco blanco), Tabebuia serratifolia (tahuari amarillo) and Terminalia oblonga (yacushapana amarilla). Results showed that Schizolobium amazonicum was the best adapted species with a fourfold height rate compared with the other species. The next best result are presented by Tabebuia serratifolia. Sites dominated by Imperata were unfavorable for the initial growth of all tree species.